Epigenetics & Chromatin - Henikoff, Steve; Grosveld, Frank
Epigenetics & Chromatin is a peer-reviewed, open access journal that publishes research, and reviews, providing novel insights into epigenetic inheritance and chromatin-based interactions. The journal aims to understand how gene and chromosomal elements are regulated and their activities maintained during processes such as cell division, differentiation and environmental alteration.